2004
DOI: 10.1186/1472-6882-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toxicity after one-months treatment with Bauhinia forficata decoction in streptozotocin-induced diabetic rats

Abstract: BackgroundPrevious experiments have shown that a decoction of Bauhinia forficata leaves reduces the changes in carbohydrate and protein metabolism that occur in rats with streptozotocin-induced diabetes. In the present investigation, the serum activities of enzymes known to be reliable toxicity markers were monitored in normal and streptozotocin-diabetic rats to discover whether the use of B. forficata decoction has toxic effects on liver, muscle or pancreas tissue or on renal microcirculation.MethodsAn experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
3
31
0
9
Order By: Relevance
“…The decreased serum amylase activities of the diabetic control rats as observed in this study is attributed to the inhibition of STZ on Ca and Mg homeostasis and amylase gene expression [30] while the increased amylase activities of the nondiabetic rats may be related to fl uctuations in the rates of amylase synthesis and its secretion by secretory glands [31,32].…”
Section: Discussionmentioning
confidence: 48%
“…The decreased serum amylase activities of the diabetic control rats as observed in this study is attributed to the inhibition of STZ on Ca and Mg homeostasis and amylase gene expression [30] while the increased amylase activities of the nondiabetic rats may be related to fl uctuations in the rates of amylase synthesis and its secretion by secretory glands [31,32].…”
Section: Discussionmentioning
confidence: 48%
“…Contradictorily, several authors demonstrated hypoglycemic effect of Bauhinia species extract or fraction. In addition, some species even has showed insulin mimetic properties and hypoglycemic action, for example B. variegata (Silva et al 2002, Pepato et al 2004, Lino et al 2004, Frankish et al 2010. Rozza et al (2015) verified that Bauhinia holophylla hydroalcoholic extract (150 mg/Kg) enhanced glutathione peroxidase (GSH-Px) and glutathione reductase (GR) activities and the reduced glutathione (GSH) level, suggesting an antioxidant activity from B. holophylla.…”
Section: Bauhinia Holophylla In Diabetic Rats 269mentioning
confidence: 99%
“…Some attempts were made to attribute the antidiabetic effects of the leaf extracts to the kaempferitrin, the major flavonoid derivative (Pinheiro et al 2006). Several studies showed the hypoglycemic effect of Bauhinia forficata (Silva et al 2002, Pepato et al 2004, Lino et al 2004, Frankish et al 2010, then other species of the same genus may have similar effect by the phylogenetic and chemistry proximity. Chemotaxonomy in conjunction with phylogenetic analysis may provide novel insights into species delimitation and chemical ecology (Kim et al 2016).…”
mentioning
confidence: 99%
“…Souza et al (2004) demonstram o efeito hipoglicêmico e potencial antioxidante do flavonóide Kaempferitrina em B. forficata, sendo confirmado o potencial contra diabetes por Pepato et al (2004) e por Menezes et al (2007), através de estudos com o decocto aquoso e com extrato aquoso, respectivamente. As folhas dessa espécie são consideradas, além de antidiabéticas, diuréticas (Silva & Cechinel Filho 2002) e hipocolesterolemiantes (Lorenzi & Matos 2002).…”
unclassified